Psychological Security and Its Role in Self-Acceptance and Self-Compassion among Football Club Players in the Iraqi Premier League (Damu Journal of Sport Sciences, 2025)
Today, educational and training sports institutions rely on scientific facts to develop their training and educational programs based on coordinated information (plans and curricula) based on the laws of various physical and human sciences. This has helped their employees, including coaches and players, manage their affairs, solve their problems, and organize their activities. Sound scientific planning for crisis management and mitigating their psychological effects requires developing a scale that can identify the level of psychological security and reassurance, and another scale that can identify self-acceptance and self-compassion, to establish the relationship between these two dimensions among football players in advanced sports clubs. This then leads to cooperation among those in charge of these clubs to find appropriate solutions. The research aims to identify the level of psychological security and self-acceptance and self-compassion among the research sample. The researcher concluded that the scales for feeling secure and self-acceptance and self-compatibility were able to measure the intended psychological variables. The level of psychological security among Iraqi Premier League football players was average. The level of self-acceptance and self-compatibility among Iraqi Premier League football players was average.